2020
DOI: 10.14336/ad.2020.0224
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Downregulated Interstitial Fluid Drainage Following Neuronal Excitation

Abstract: The drainage of brain interstitial fluid (ISF) has been observed to slow down following neuronal excitation, although the mechanism underlying this phenomenon is yet to be elucidated. In searching for the changes in the brain extracellular space (ECS) induced by electrical pain stimuli in the rat thalamus, significantly decreased effective diffusion coefficient (DECS) and volume fraction (α) of the brain ECS were shown, accompanied by the slowdown of ISF drainage. The morphological basis for structural changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Significantly disturbed ISF drainage has been observed in a demyelinated rat model caused by chemical toxicity [ 6 ]. A recent study by Li et al demonstrated downregulated ISF drainage following neuronal excitation [ 13 ]. The study showed that the reduced ISF drainage was caused by the slow diffusion in ECS and the release of excitatory neurotransmitters, including glutamate, glutamine, N-acetylaspartate, and aspartate [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Significantly disturbed ISF drainage has been observed in a demyelinated rat model caused by chemical toxicity [ 6 ]. A recent study by Li et al demonstrated downregulated ISF drainage following neuronal excitation [ 13 ]. The study showed that the reduced ISF drainage was caused by the slow diffusion in ECS and the release of excitatory neurotransmitters, including glutamate, glutamine, N-acetylaspartate, and aspartate [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Li et al demonstrated downregulated ISF drainage following neuronal excitation [ 13 ]. The study showed that the reduced ISF drainage was caused by the slow diffusion in ECS and the release of excitatory neurotransmitters, including glutamate, glutamine, N-acetylaspartate, and aspartate [ 13 ]. Under different anesthesia, the release of noradrenaline (NA) in the brain ECS could also determine the drainage rate of ISF [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Is the activity of AQP4 channels somehow responsible for this inversed relationship between neurovascular coupling and glymphatic flow? Indeed, the trend to the physiological flow reduction in regions of neuronal activation was reversed in AQP4 knockouts ( 171 ). AQP4 expression and polarization are also strongly dependent on circadian rhythm ( 162 , 172 ), suggesting that proper AQP4 activity is required for physiological glymphatic stagnancy in periods/areas of neuronal excitation.…”
Section: Aquaporin 4: Its Physiological Functionmentioning
confidence: 99%